2019
DOI: 10.1103/physrevb.99.155156
|View full text |Cite
|
Sign up to set email alerts
|

Theory of partial quantum disorder in the stuffed honeycomb Heisenberg antiferromagnet

Abstract: Recent numerical results [Gonzalez et al., Phys. Rev. Lett. 122, 017201 (2019); Shimada et al., J. Phys. Conf. Ser. 969, 012126 (2018)] point to the existence of a partial-disorder ground state for a spin-1/2 antiferromagnet on the stuffed honeycomb lattice, with 2/3 of the local moments ordering in an antiferromagnetic Néel pattern, while the remaining 1/3 of the sites display short-range correlations only, akin to a quantum spin liquid. We derive an effective model for this disordered subsystem, by integrat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 42 publications
4
13
0
Order By: Relevance
“…A similar seperation of ordered and disordered phases has also been reported for Cu 2 IrO 3 [29] and Li 2 RhO 3 [30]. Theoretical treatment of such phenomena revealed that the ground state is stabilized from competition between quantum fluctuation and frustration [31,32]. We wish to note the fact that a relatively large impurity phase is present in the compound, which could be the origin behind the anomaly around T C .…”
Section: Discussionsupporting
confidence: 72%
“…A similar seperation of ordered and disordered phases has also been reported for Cu 2 IrO 3 [29] and Li 2 RhO 3 [30]. Theoretical treatment of such phenomena revealed that the ground state is stabilized from competition between quantum fluctuation and frustration [31,32]. We wish to note the fact that a relatively large impurity phase is present in the compound, which could be the origin behind the anomaly around T C .…”
Section: Discussionsupporting
confidence: 72%
“…In the honeycomb structure family, frustration is known to cause partial magnetic disorder. This leads to a spin liquid or spin glass like ground states, which is often hidden behind a long-range magnetic ordering 22 24 . Here the SR technique is uniquely capable of detecting such mixed state, including its volume fractions.…”
Section: Resultsmentioning
confidence: 99%
“…The classical phase diagram of this model was found in Ref. 21, while previous work has also examined a region of partial (C sublattice) disorder near the honeycomb limit with only nearest neighbor couplings 15,[28][29][30][31] ; further neighbor couplings will remove this region of partial disorder as they induce independent C spin order.…”
Section: Introductionmentioning
confidence: 99%